Red cell alloimmunization and infectious marker status (human immunodeficiency virus, hepatitis B virus and hepatitis C virus) in multiply transfused thalassemia patients of North India - Raj Nath Makroo; Jatinder Singh Arora; Mohit Chowdhry; Aakanksha Bhatia; Uday Kumar Thakur; Antony Minimol (Wolters Kluwer Medknow Publications, 2013)
Background: Patients with thalassemia major are largely transfusion dependent and are thus exposed to a variety of risks such as transmission of infectious diseases, iron overload and alloimmunization. This study was performed to determine the prevalence of human immune deficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV) and red cell antibodies among multiple-transfused thalassemic patients in and around the national capital region. Materials and Methods: The Department of Transfusion Medicine, Indraprastha Apollo Hospitals, conducted this study in collaboration with the National Thalassemia Welfare Society over a period of 1 year starting February2011. Blood samples from the patients were tested for blood group, red cell alloantibody/ies, anti-HIV, anti-HCV and hepatitis B surface antigen (HBsAg) by ELISA and for the respective viral ribonucleic acid (RNA) or deoxyribonucleic acid (DNA) by nucleic acid testing (NAT). Results: A total of 462 thalassemics which consists of 290 males and 172 females were tested. The overall alloimmunization rate was 4.1% and anti-Kell was the most common antibody identified. Thirteen cases (2.8%) were positive for HBsAg by ELISA, 107 (23.1%) were reactive for anti HCV and 11 (2.38%) for anti HIV antibodies. Further screening and discriminatory assays by NAT confirmed the presence of HBV DNA in 11 cases, HIV RNA in 7 cases and HCV RNA in 48 cases. Conclusion: In spite of advances in Immunohematology and infectious marker testing in recent years, the rates of alloimmunization and infectious marker positivity remains high among multiply transfused patients like thalassemics. Provision of safe and adequate blood supply to these patients is a key to improving their quality-of-life and longevity.